2016
DOI: 10.1103/physrevb.93.161109
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of bulk second-harmonic generation inside a glass slide with tightly focused optical fields

Abstract: Bulk second-harmonic generation (SHG) inside glass slides is directly detected unambiguously without interference from surface contributions. This is enabled by tightly focused and highly localized ultrashort laser pulses. The theoretical calculations based on vector diffraction theory and the phenomenological model of SHG inside centrosymmetric materials agree well with the measured far-field SHG radiation patterns for different polarization states of the fundamental beam. The results indicate that the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, key parameters are the control of viscosity and crystal nucleation and growth which tends to minimize the extrinsic scattering loss due to the presence of crystals during glass preform and fiber fabrication [19]. Further examinations in the glass-ceramic in the system of TeO 2 -GeO 2 will be performed in order to obtain a laser emission and second harmonic generation [37,38]. Glass features mentioned above can be controlled by the analysis of the thermal properties and for that purposes, differential scanning calorimetry (DSC) is commonly used [19,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, key parameters are the control of viscosity and crystal nucleation and growth which tends to minimize the extrinsic scattering loss due to the presence of crystals during glass preform and fiber fabrication [19]. Further examinations in the glass-ceramic in the system of TeO 2 -GeO 2 will be performed in order to obtain a laser emission and second harmonic generation [37,38]. Glass features mentioned above can be controlled by the analysis of the thermal properties and for that purposes, differential scanning calorimetry (DSC) is commonly used [19,29].…”
Section: Introductionmentioning
confidence: 99%
“…Both bulk and surface SHG excited by tightly focused laser beams have been earlier studied theoretically and experimentally in different media, including isolated centrosymmetric nanospheres 40,41 , metal nano-objects 42 , glass slides 43,44 and silicon nanowires 45 . The obtained results in particular have shown that analysis of SHG radiation patterns enables separating the second-harmonic response stemming from different elements of the surface nonlinear tensor 40,41,45 , different contributing terms in the bulk quadrupolar response 40,41,43 or distinguishing the surface and bulk signals 40,44 . However, it is important to emphasize here that all aforementioned works dealt with SHG from centrosymmetric materials only.…”
Section: Tightly-focused Gaussian Beam Illuminationmentioning
confidence: 99%